A Study of Structural Changes Embed in Surface Diffusion Layer of Carbon Steel ST-20 Nitrided in Ammonia Furnace 〖NH〗_3 (Latakia University Journal -Basic Sciences Series, 2019)
We have studied in this paper the effects of thermal gaseous treatment using NH3 – gas in thermal furnace , those effects are on diffusion layers properties of carbon steel nitrided in temperatures (550 ,650 ,750, 850,950) 0C, at  for each temperature. The micro-hardness was determined using Vickers's tester with results value ranged between (130-482) HV. We studied the formed microstructure of the surface layers by using X-ray diffraction technique XRD, the profile of surface layers was studied by metallurgical microscope. We verify the increase of thickness hard diffusion layer as increase of nitride temperature. Nitrided phases  and  appeared in microstructure, while the Bainite structure   appeared when temperature increased up to . The results showed that the hardness increased by increasing in nitride diffusion layer and changing of phases suites.